An empirical model of carbon flow through marine viruses and microzooplankton grazers. (7th May 2019) - Talmy, David; Beckett, Stephen J.; Taniguchi, Darcy A. A.; Brussaard, Corina P. D.; Weitz, Joshua S.; Follows, Michael J.
Summary: Viruses and microzooplankton grazers represent major sources of mortality for marine phytoplankton and bacteria, redirecting the flow of organic material throughout the world's oceans. Here, we investigate the use of nonlinear population models of interactions between phytoplankton, viruses and grazers as a means to quantitatively constrain the flow of carbon through marine microbial ecosystems. We augment population models with a synthesis of laboratory‐based estimates of prey, predator and viral life history traits that constrain transfer efficiencies. We then apply the model framework to estimate loss rates in the California Current Ecosystem (CCE). With our empirically parameterized model, we estimate that, of the total losses mediated by viruses and microzooplankton grazing at the focal CCE site, 22 ± 3%, 46 ± 27%, 3 ± 2% and 29 ± 20% were directed to grazers, sloppy feeding (as well as excretion and respiration), viruses and viral lysate respectively. We identify opportunities to leverage ecosystem models and conventional mortality assays to further constrain the quantitative rates of critical ecosystem processes.